2009
DOI: 10.1016/j.seares.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic and mechanistic model of PCB bioaccumulation in the European hake (Merluccius merluccius)

Abstract: Bioaccumulation is difficult to document because responses differ among chemical compounds, with environmental conditions, and physiological processes characteristic of each species. We use a mechanistic model, based on the Dynamic Energy Budget (DEB) theory, to take into account this complexity and study factors impacting accumulation of organic pollutants in fish through ontogeny. The bioaccumulation model proposed is a comprehensive approach that relates evolution of hake PCB contamination to physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
1
35
1
1
Order By: Relevance
“…Generally, the trend of tissue content variation was as follows: gonad [ liver [ muscle. Bodiguel et al (2009) reported for the European hake (Merluccius merluccius), greater energy allocation to growth for female fish and a transfer of PCBs from the female fish to eggs when allocating lipids from reserve to eggs.…”
Section: Pollutant Levels In Roach Chub and Perch Musclementioning
confidence: 94%
“…Generally, the trend of tissue content variation was as follows: gonad [ liver [ muscle. Bodiguel et al (2009) reported for the European hake (Merluccius merluccius), greater energy allocation to growth for female fish and a transfer of PCBs from the female fish to eggs when allocating lipids from reserve to eggs.…”
Section: Pollutant Levels In Roach Chub and Perch Musclementioning
confidence: 94%
“…It is capital to link any toxico-kinetic module with the energetics of the organism (e.g. van Haren et al, 1994;Bodiguel et al, 2009;Ng and Gray, 2009;Eichinger et al, 2010). However the details around how water chemistry (e.g.…”
Section: Deviations From the Extended One Compartment Toxico-kinetic mentioning
confidence: 99%
“…In a similar way, contaminant analyses can discriminate between two organic matter (OM) sources with similar isotopic ratios but different contamination levels (Cresson et al, 2014;McMeans et al, 2014). Finally, contamination levels and stable isotope ratios are under the control of different metabolic and environmental processes, such as local contamination source, growth rate or primary production intensity (Fisk et al, 2001(Fisk et al, , 2002Hoekstra et al, 2003;Bodiguel et al, 2009aBodiguel et al, , 2009bDierking et al, 2009;Cossa et al, 2012;Harmelin-Vivien et al, 2012a). Combining the results provided by these techniques was thus recently used as an effective tool to discriminate between different local populations influenced by different environmental conditions or contaminant sources (Carravieri et al, 2014;Chouvelon et al, 2014;Brown et al, 2015;Lavoie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%